1970
DOI: 10.1063/1.1673876
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Pseudorotation, and Vibrational Mode Coupling in IF7: An Electron Diffraction Study

Abstract: Free vapor-phase molecules of iodine heptafiuoride are pentagonal bipyramids with axial bonds (1.786± 0.007 A esd) shorter than equatorial bonds (1.858±0.004 Al. They are deformed from Doh symmetry on the average by 7.5 0 ring puckering displacements (e2" symmetry) and 4.5 0 axial bend displacements (e,' symmetry). The distortion from Doh, interpreted in terms of the points-on-a-sphere variant of the valence-shell electron-pair theory, is compatible with an effective force law between electron pairs of Vij""' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 50 publications
(4 reference statements)
4
20
0
Order By: Relevance
“…To explain the NMR equivalence of all fluorine atoms in both compounds, the 'chimeric pseudorotation' mechanism proposed for IF 7 (Cass et al, 2006) can be taken into account. Apical/equatorial exchange in IF 7 , first analyzed by Bartell (Adams et al, 1970) showed fluxional behavior of mixed character: Berry-like bending motion (Berry, 1960), turnstile rotation and lever mechanisms. One can also expect similar dynamic exchange in our case.…”
Section: F Nmr Datamentioning
confidence: 99%
“…To explain the NMR equivalence of all fluorine atoms in both compounds, the 'chimeric pseudorotation' mechanism proposed for IF 7 (Cass et al, 2006) can be taken into account. Apical/equatorial exchange in IF 7 , first analyzed by Bartell (Adams et al, 1970) showed fluxional behavior of mixed character: Berry-like bending motion (Berry, 1960), turnstile rotation and lever mechanisms. One can also expect similar dynamic exchange in our case.…”
Section: F Nmr Datamentioning
confidence: 99%
“…Without this protocol, any monovacant tetrahedral nitrogen atom with three different binding sites is a stereocenter. If none of the ligands are linked in a trigonal or pentagonal bipyramid, axial and equatorial ligands interchange at room temperature through Berry pseudorotation [34 ] and the Bartell mechanism [35 ], respectively. Molassembler will therefore 'thermalize' stereopermutations in such shapes in the thawing approximation if none of the binding sites are linked, reducing such shapes' chiral character.…”
Section: Atom-centered Stereopermutatorsmentioning
confidence: 99%
“…The isolated IF 7 molecule has the form of a pentagonal bipyramid belonging to the symmetry group D 5h , in which the bonds of the apical F-I-F unit are shorter than those of the more congested equatorial IF 5 unit; the mean I-F distance is shorter than that observed in IF 5 , despite the increased crowding. However, the details of the electron-diffraction pattern 896 imply that the molecule is deformed from D 5h symmetry on the average by puckering of the equatorial ring of fluorine atoms and by bending of the axial F-I-F unit, the angular displacements about the central atom being 7-5° and 4-5°, respectively. The simplest interpretation of the diffrac tion intensities is that the molecule undergoes essentially free pseudorotation, involving facile intramolecular rearrangement, along a pathway (predominantly described by e 2 " displacement coordinates) connecting 10 equivalent structures of C 2 symmetry via inter mediates of C s symmetry.…”
Section: C1f 3 893 and Brfmentioning
confidence: 99%
“…The most precise estimates of the interatomic distances in the diatomic molecules come from the microwave spectra and from the rotational detail observed at high resolution in the electronic spectra of the gaseous materials 891 3 894 microwave studies of the vapours again provide definitive structural details, while the combination of microwave and electron-diffraction measurements has recently enabled the structures of BrF 5 and IF5 to be determined with some confidence 895 . Electron diffraction also forms the basis of the most detailed structural analysis so far carried out on the IF 7 molecule in the vapour phase 896 . The geometry of C1F 5 has been deduced from its vibrational and 19 Fnmr spectra; though consistent with the vibrational properties, the approximate dimensions given in the table are prompted largely by analogy with related molecules.…”
Section: If 5 (G) ► If 3 (G)+2f(g)838mentioning
confidence: 99%